Global Trends of Treatment for NAFLD from 2012 to 2021: A Bibliometric and Mapping Analysis - Song, Yuling; Chen, Boru; Jiang, Lu; Zhao, Fangkun; Feng, Xiuqin (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Aim: The present study aimed to map publication trends and explore research hotspots of treatment for NAFLD study by bibliometric analysis. Background: Nonalcoholic fatty liver disease (NAFLD) is a multi-system metabolic disorder involving the liver. Thousands of papers have been published on the treatment of NAFLD, but no comprehensive statistical and intuitive analysis has been made. The present study aimed to map publication trends and explore research hotspots of treatment for NAFLD study by bibliometric analysis. Objective: (1) The pathogenesis of NAFLD and the possible treatment mechanism; (2) prevalence, risk factors, and traditional therapies for NAFLD; (3) frontier therapies for NAFLD. Method; This paper conducted a bibliometric analysis based on the Web of Science Core Collection (WoSCC). The knowledge map was constructed by VOS viewer v.1.6.10 to visualize the annual publication number, the distribution of countries, international collaborations, author productivity, source journals, cited references, and keywords in this field. Results: From 2012 to 2021, 2,437 peer-reviewed publications on the treatment of NAFLD were retrieved. China contributed the most publications, while the United States received the most citations. Journal of Hepatology was the most prolific journal in this field. Prof. Rohit Loomba. Conclusion: Our study provides a comprehensive and objective analysis of NAFLD treatment that allows researchers to quickly locate research hotspots in a large number of relevant literatures. Meanwhile, it may also provide valuable information for researchers looking for potential partners and institutions.
Keywords: woSCC